Psychological status and related factors of resident physicians during the release of COVID-19 pandemic restrictions in China - Zhang, Qing; Pan, Ruibo; Pan, Qi; Qian, Yandan; Zhou, Xiao; Chen, Qiaozhen (Frontiers in Public Health, 2024)
Background Resident physicians at the standardized training stage had undergone significant physical and mental stress during the release of the COVID-19 pandemic restrictions at the end of 2022 in China. This study aimed to investigate the psychological status (including anxiety, depression, somatic symptoms, job burnout, and vicarious trauma) of resident physicians and identify its influencing factors under these special periods. Methods Survey was conducted one month after the release of the COVID-19 pandemic restrictions on resident training physicians from a tertiary first-class hospital in Zhejiang, China. Resident physicians completed the psychological status questionnaire. Chi-square tests, Mann-Whitney U tests, and logistic regression analyses were used to estimate the group differences and variable associations.The prevalence of anxiety, depression, and somatic discomfort in this study was 20.88%, 28.53%, and 41.47%, respectively. Female resident physicians were more likely to experience somatic symptoms [adjusted odds ratio (OR) = 2.36, 95% confidence interval (CI): 1.33-4.18]. Resident physicians with problem-focused coping styles were less prone to psychological health issues [depression (adjusted OR = 0.92, 95% CI: 0.88-0.96), anxiety (adjusted OR = 0.94, 95% CI: 0.90-0.98), somatic symptoms (adjusted OR = 0.93, 95% CI: 0.89-0.97), job burnout (adjusted OR = 0.91, 95% CI: 0.87-0.96) and vicarious trauma (adjusted OR = 0.94, 95% CI: 0.90-0.98)]. Inversely, resident physicians with emotion-focused coping styles and experienced negative life events were more prone to psychological health issues.Resident training physicians had a high risk of anxiety, depression, and somatic symptoms under the special COVID-19 pandemic restriction release period. Females, with lower training stages, degrees, negative life events, and emotion-focused coping styles had a disadvantaged effect on psychological status. The medical teaching management department needs to monitor and reduce the workload and working hours of resident physicians, ensure sufficient sleep time, and pay attention to the psychological status of resident physicians. By strengthening regular communication and mental health education or intervention, which can help them improve their ability to cope with complex tasks.